Necessity of a repeat cholangiogram during biliary stent removal after postcholecystectomy bile leak - Jain, Vishal (Pulsus Group Inc, 2012)
PURPOSE: To assess the need for repeat endoscopic retrograde cholangiography (ERC) in patients undergoing biliary stent removal after management of postcholecystectomy bile leak. METHODS: A retrospective analysis of the Clinical Outcomes Research Initiative endoscopy database at PennState Milton S Hershey Medical Center (Hershey, Pennsylvania, USA) identified all patients referred for ERC with an indication of postcholecystectomy bile leak from January 2001 to June 2010. Baseline demographics, location of bile leak, size of biliary stent placed, duration of stenting, bile leak persistence, and the presence of stone, sludge or strictures on repeat ERC were analyzed. RESULTS: A total of 81 patients underwent ERC for management of bile leaks after cholecystectomy. One patient was excluded due to a complete transection of the common bile duct necessitating immediate surgical intervention. Fourteen (17.5%) patients underwent open cholecystectomy, 46 (57.5%) underwent laparoscopic procedures and 10 (12.5%) procedures were converted from a laparoscopic to an open approach intraoperatively. Of the 80 patients, 47 (58.7 %) had a cystic duct leak, 11 (13.7 %) had a right hepatic duct leak, 11 (13.7%) had a common bile duct leak, five (6.2%) had a gallbladder fossa leak, four (5%) had a common hepatic duct leak and the remaining two (2.5%) had a left hepatic duct leak. All 80 patients underwent biliary stenting as part of management for their bile leak. Fifty-seven of the 80 patients (71.2%) had a 10 Fr stent placed, with the remainder undergoing placement of a 7 Fr stent. Seventy-five (93.7%) patients underwent biliary sphincterotomy during the initial ERC. Sixty-nine patients underwent repeat ERC after a mean duration of 8.2 weeks (range 0.4 to 18.5 weeks). Eleven patients had no reviewable records regarding a repeat procedure performed for stent removal. Three patients required an early repeat ERC due to suspicion of cholangitis and, hence, were excluded from the final analysis. Of the 66 patients included in the final analysis, 61 (92.4%) had resolution of their bile leak on repeat ERC. All patients had resolution of their bile leak by the third ERC. Fifteen patients (22.7%) had an abnormality on repeat cholangiography (persistent leak in four, stones in three, sludge in seven, and a combination of leak and stone in one) that required further endoscopic intervention including balloon sweep or additional stenting. CONCLUSION: Although the majority of postcholecystectomy bile leaks resolve after biliary stent placement, a sizeable percentage (22.7%) of patients had abnormalities on subsequent cholangiograms that required further intervention. These findings suggest the need for a repeat ERC at the time of biliary stent removal in the management of postcholecystectomy bile leaks.